2021
DOI: 10.3390/jmse9030266
|View full text |Cite
|
Sign up to set email alerts
|

Rise, Fall, and Recovery of Blockchains in the Maritime Technology Space

Abstract: Blockchain technology, since its introduction, has been expected to be implemented in many areas. Cryptocurrency is one unique example that established a functioning application. On the other hand, blockchain technology is not immune to various challenges related to the nature of itself, privacy management, and antitrust laws, among others. This study lays out the nature of blockchain and applications in the maritime industry, while highlighting the bottlenecks. Potential resolutions and anticipated developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…Perishable goods are tracked via blockchain as they are moved across continents. Supply chain partners, as well as border, customs, and port officials, are all involved in these initiatives (Pu and Lam, 2020;Munim et al, 2021). Walmart is also beginning to implement blockchain across its supply chain, from cultivation, manufacturing, processing, and distribution, to warehousing and retail (Zhao et al, 2016;Bai et al, 2022).…”
Section: Application Of Blockchain In Supply Chain Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Perishable goods are tracked via blockchain as they are moved across continents. Supply chain partners, as well as border, customs, and port officials, are all involved in these initiatives (Pu and Lam, 2020;Munim et al, 2021). Walmart is also beginning to implement blockchain across its supply chain, from cultivation, manufacturing, processing, and distribution, to warehousing and retail (Zhao et al, 2016;Bai et al, 2022).…”
Section: Application Of Blockchain In Supply Chain Managementmentioning
confidence: 99%
“…Perishable goods are tracked via blockchain as they are moved across continents. Supply chain partners, as well as border, customs, and port officials, are all involved in these initiatives (Pu and Lam, 2020; Munim et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…in shore control centres and other shore-based infrastructures) (Bolbot et al 2020), we argue that current maritime practices should be adjusted to suit the evolving scenario of autonomous shipping to maintain the sustainable future of the maritime industry. Going forward, increased implementation of Internet-of-Things (IoT), based on blockchain technology platforms for managing operations, might mitigate vulnerability to cyber security to some extent (Munim et al 2021).…”
Section: Implications For the Maritime Industrymentioning
confidence: 99%
“…Munim et al [19] identified the main challenges in the practical application of BC in the maritime sector as lack of standardization of data elements, lack of interoperability and scalability between systems, delay in legislation, lack of understanding of the technology, and lack of training facilities and materials. PiChain is facing the same challenges as it uses BC technology.…”
Section: A Case Study Of Pi and Blockchain Technology For Smart Portsmentioning
confidence: 99%